OBESITY PROFILE AS A RISK FACTOR IN RENAL CELL CARCINOMA PATIENTS: A LITERATURE REVIEW - Ilham Bagas Setyawan; Ferry Safriadi (Indonesian Journal of Urology, 2025)
Objective: This study aims to determine the profile of obesity as a risk factor for developing RCC. Material & Methods: This study is a library research study with journals, articles, and opinions of related experts taken from Google Scholar and Pubmed which was uploaded in 2019-2023. Results: 7 articles met the inclusion, exclusion and topic relevance criteria. Several journals stated that obesity is a strong risk factor for the development of renal cell carcinoma (RCC), although opposite results were found in one study regarding obesity and the prognostic outcome of RCC patients. Discussion: The mechanism of obesity in increasing the risk of RCC is a complex process, which involves the process of insulin resistance, inflammation by pro-inflammatory cytokines, angiogenesis, and proliferative effects as a result of the role of insulin as one of the most important anabolic hormones capable of stimulating cell proliferation, and is exacerbated by imbalanced cell anti-apoptotic mechanisms. Conclusion: No relationship was found between the lipid profile and the incidence of RCC. Little research has been done on lipid profiles for RCC, considering that the largest RCC subtype, ccRCC, is characterized by the accumulation of lipids and glycogen, which has implications for changes in fatty acid and glucose metabolism in its etiology. Further studies are needed to examine the effect of lipid profiles on the risk of renal cell carcinoma. Keywords: Carcinogenesis, obesity profile, renal cell carcinoma.